2010
DOI: 10.1007/s10450-010-9300-8
|View full text |Cite
|
Sign up to set email alerts
|

Boron adsorption mechanism on polyvinyl alcohol

Abstract: Recently, an increase in the use of boron compounds has led to an increase in boron emissions, and concern has grown regarding its detrimental effects on the human body. An adsorbent that adsorbs boron selectively has been developed as a countermeasure. Although certain commercially available boron selective adsorbents can be used to remove boron from aqueous solutions by utilizing the strong affinity between boron and hydroxyl groups, the adsorption capacity appears to be insufficient. So, we adopted polyviny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 28 publications
1
16
0
1
Order By: Relevance
“…Although the maximum boron concentration in drinking water in World Health Organization is 2.4 mg/L, tougher standards at 1.0 mg/L were established in many them, hydroxyl-containing boron-selective adsorbents are considered to be one of the best promising materials for boron removal [8,14,15], such as the boron specific resin (such as IRA743, CRB 05), which is the most representative adsorbent for borate. However, the higher production cost of resin is a great shortage [16]. Therefore, numerous low cost adsorbents and waste products have been investigated in recent years [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although the maximum boron concentration in drinking water in World Health Organization is 2.4 mg/L, tougher standards at 1.0 mg/L were established in many them, hydroxyl-containing boron-selective adsorbents are considered to be one of the best promising materials for boron removal [8,14,15], such as the boron specific resin (such as IRA743, CRB 05), which is the most representative adsorbent for borate. However, the higher production cost of resin is a great shortage [16]. Therefore, numerous low cost adsorbents and waste products have been investigated in recent years [17].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum sorption capacity of LDH-D-900 was 1.34 mmol/g, which is close to the 1.29 mmol/g and 1.20 mmol/g for LDHs prepared from chemical reagents by Ferrier et al 12) and Jiang et al 13) The borate sorption capacity of LDH-D-900 was also similar to that reported previously for CRB 05, a kind of borate-specific resin. 14) Because LDH-D-900 showed better sorption performance than LDH-D-675, the solid residues of LDH-D-900 were collected after the sorption experiment and characterized by 11 B MAS NMR to explore the sorption mechanism ( Fig. 5).…”
Section: Sorption Of Borate By D-ldhmentioning
confidence: 99%
“…Bor pek çok endüstri için oldukça faydalı bir bileşendir. Bor bileşikleri ilaç üretiminden metal endüstrisine kadar geniş bir aralıkta kullanılmaktadır [25]. Cam endüstrisi dünyadaki toplam bor bileşiklerinin üretiminin yarıdan fazlasını kullanan en önemli endüstridir.…”
Section: Dünyadaki Ve Türkiye'deki Bor Yataklarıunclassified